Efeitos de uma intervenção educativa sobre o conhecimento e parâmetros bioquímicos e antropométricos de pacientes diabéticos - Santos, Cláudia Ribeiro de Lima (2016)
Diabetes Mellitus (DM) is a non-communicable chronic disease with high prevalence and high social cost. The DM is among the leading causes of mortality in the world. The aim of this study was to analyze the effect of an educational intervention, based on social cognitive theory, on knowledge, and on biochemical and anthropometric parameters o patients with type 2 diabetes. A randomized clinical trial was conducted with 83 patients with type 2 diabetes non-insulin dependent, of both sexes, registered in a Family Health Strategy (ESF), in Israelândia-Go in 2015. The final sample consisted of 76 participants with type 2 diabetes divided into two groups, intervention (GI = 38) and control (GC = 38). The GI participated in the educational intervention, based on social cognitive theory, from September 2015 to February 2016. The GC did not attend the educational intervention, but continued participating in the activities developed monthly by to ESF in the Hiperdia. Data were collected in the GC during activities in Hiperdia; and in GI during educational activities. The study was conducted in four stages: 1 stage formation of groups (GI and GC), step 2 - the questionnaires (pre-intervention), and collection of biochemical and anthropometric data, step 3-educational intervention in GI, step 4 application of questionnaires and collection of biochemical and anthropometric data (post-intervention). In steps 2 and 4, was applied in both groups, the Knowledge Questionnaire Diabetes and evaluated parameters of control: weight, body mass index (BMI), waist circumference (WC), blood glucose and glycated hemoglobin (HbA1c ) were evaluated in these steps. Data processing was carried out in the program-Stata (SE version. 64). The Shapiro-Wilk test for normality was used to determine the normality of the data. Chi-square and tStudent tests were used to analyze categorical and numerical variables, respectively, with a 5% significance level. The results point to a significant increase in knowledge in all aspects addressed to GI (p <0,001). In relation to the metabolic control, GI showed a decrease of HbA1c (p <0,001) and waist circumference (p <0,001) compared to CG. In conclusion, after the educational intervention, there was an improvement in knowledge about diabetes, biochemical and anthropometric parameters, which suggests the importance of self-efficacy (AE) for empowerment of knowledge and control of DM.